Brand strategies development through sales promotion and endorsement of Small and Medium Enterprises (SME) in West Java Indonesia (Research, Society and Development, 2021)
Not all business in the market get customer attentions as they deserve, especially for Small Medium Enterprise (SME). It sparks fierce competition between SME to stand out from rivals in the market. Sales promotion is known as one of the most effective method which influence sales volume, especially for SME’s market. The second strategy is having endorsement from a third-party. Previous studies have identified impact of monetary promotion through online and in-store strategy to build strong brand identity without, and so as endorsement. However, there is still inadequate understanding of branding development particularly what specific promotions and endorsement works better for SME, as previous research are mostly based on multinational or big firms which have different characteristics with SME. Therefore, this paper examine the impact of two types of promotions, which are: monetary (vs non-monetary) promotion and celebrity (vs.non-celebrity) endoresement into better customer perceptions about SMEs’ product and brand.